Pengembangan E-Modul Thaharah untuk Tingkat Sekolah Dasar - Amalia Hasanah; Wido Supraha; Rudi Hartanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the development of thaharah E-Module media which can help Bogor City Elementary School students. To increase understanding of teaching materials about the methods of thaharah. Apart from that, it makes it easier for educators into convey the content of the material in an interesting and interactive manner. The method used is literature, this type of research method uses libraries (library research) by collecting not just books but also documentation materials, magazines, journals and newspapers, this research emphasizes determining various theories, laws, postulates, principles, opinions, ideas and others that can be used to analyze and solve the problem being studied. The relevant research results show that the use of the thaharah e-module has experienced a significant increase in learning outcomes. In fact, the method that is widely used by educators in the field is mostly the lecture method, therefore the development of electronic media for thaharah modules regarding material learning is able to simplify and improve the quality of students' understanding of thaharah material.